The Influence of Work Factors, Organizational Culture, and Working Behavior Affecting the Job Performance of Operational Employees in the Food and Beverage Industry in Laem Chabang Industrial Estate, Chonburi Province - Kullachart, Rutcharin; Saraphat, Somboon; Boonriw, Paraunyoo (Journal of Industrial Business Administration, 2023)
The main objective of this research was to the influence of work factors, organizational culture, and working behavior affecting the job performance of operational employees in the food and beverage industry in Laem Chabang industrial estate, Chonburi province. This research employed the survey research method. A questionnaire was used to collect data from the sample consisting of 294 operational employees in the food and beverage industry in Laem Chabang industrial estate. The quantitative data were analyzed using descriptive statistics of percentage, mean, and standard deviation, and inferential statistics of simple and multiple regression analyses. The results indicated that work factors, organizational culture, and working behavior affect job performance with a statistical significance of 0.05 level.